2016
DOI: 10.3928/02793695-20160920-06
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Six Core Strategies for Restraint Minimization in a Specialized Mental Health Organization

Abstract: Implementation of the Six Core Strategies to Reduce the Use of Seclusion and Restraint (Six Core Strategies) at a recovery-oriented, tertiary level mental health care facility and the resultant changes in mechanical restraint and seclusion incidents are described. Strategies included increased executive participation; enhanced staff knowledge, skills, and attitudes; development of restraint orders and decision support in the electronic medical record to enable informed debriefing and tracking of events; and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…There was a 19.7% decrease in the number of restraint and seclusion incidents, a 42.3% decrease in the total restraint and seclusion hours, and a 38.9% decrease in the average hours per restraint or seclusion from the 2011/2012 fiscal year to the 2013/2014 fiscal year [18]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a 19.7% decrease in the number of restraint and seclusion incidents, a 42.3% decrease in the total restraint and seclusion hours, and a 38.9% decrease in the average hours per restraint or seclusion from the 2011/2012 fiscal year to the 2013/2014 fiscal year [18]. …”
Section: Resultsmentioning
confidence: 99%
“…To align practices with recovery values, a policy supporting least restraint and seclusion was implemented [18]. Decision support was embedded directly within the physician orders for restraint and seclusion, and appropriate documentation of best practices were reflexed for clinical staff.…”
Section: Methodsmentioning
confidence: 99%
“…While other strategies aimed towards restraint minimization had been implemented prior to and during the follow‐up period of the present study (Riahi et al . ), regression analysis of the effects of multidimensional restraint‐minimization strategies in a similar public hospital specializing in the treatment of serious and persistent mental illness showed that administrative review of practices was the most important strategy (Donat ). This suggests that despite changing factors in the hospital, recovery rounds were an important initiative that affected restraint practices.…”
Section: Discussionmentioning
confidence: 99%
“…For most measures, however, analysis showed a change in the trends for seclusion and restraint at the time of implementation. Visual examination of the corporate restraint and seclusion summary data showed a prominent change in overall restraint and seclusion hours in December 2012, when recovery rounds were implemented, which remained lower thereafter (Riahi et al 2016). Trends otherwise appeared relatively consistent, despite ongoing efforts towards restraint minimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation